2018
DOI: 10.3389/fmars.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns in the Coral Reef Communities of the Spermonde Archipelago, 2012–2014, II: Fish Assemblages Display Structured Variation Related to Benthic Condition

Abstract: The Spermonde Archipelago is a complex of ∼70 mostly populated islands off Southwest Sulawesi, Indonesia, in the center of the Coral Triangle. The reefs in this area are exposed to a high level of anthropogenic disturbances. Previous studies have shown that variation in the benthos is strongly linked to water quality and distance from the mainland. However, little is known about the fish assemblages of the region and if their community structure also follows a relationship with benthic structure and distance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Proliferation of colonial ascidians has also been reported on several reefs after increases in nutrient availability and overfishing 58 , 61 . Increases in these organisms can have severe effects on reef health and functioning by altering reef replenishment, geomorphology and trophic structure 58 , 62 , 63 . Here, we observed that the two communities dominated by potentially proliferating organisms displayed simultaneously the lowest fish and benthic functional diversities, including the lowest diversity and cover of reef-building functional entities, such as branching corals.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation of colonial ascidians has also been reported on several reefs after increases in nutrient availability and overfishing 58 , 61 . Increases in these organisms can have severe effects on reef health and functioning by altering reef replenishment, geomorphology and trophic structure 58 , 62 , 63 . Here, we observed that the two communities dominated by potentially proliferating organisms displayed simultaneously the lowest fish and benthic functional diversities, including the lowest diversity and cover of reef-building functional entities, such as branching corals.…”
Section: Discussionmentioning
confidence: 99%
“…Benthic communities were quantified in parallel with Teichberg et al (2018) and Plass-Johnson et al (2018). At each island there were 50 photographic quadrats per 50 m transect.…”
Section: Benthic Community Assessmentmentioning
confidence: 99%
“…There have been studies on various aspects of reef health and biodiversity across this gradient in the Spermonde Islands over the past decades (Moll 1983;Best et al 1989;CRITC 2012;Hoeksema 2012b), as well as more recent studies on coral reefs and associated biodiversity (Plass-Johnson et al 2018a;Plass-Johnson et al 2018b;Teichberg et al 2018). However, there is a need for updated and/or complementary data on certain aspects of coral community biodiversity, ecology and health.…”
Section: Introductionmentioning
confidence: 99%